2021
DOI: 10.3892/ol.2021.13021
|View full text |Cite
|
Sign up to set email alerts
|

Association between the expression of core 3 synthase and survival outcomes of patients with cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is a highly aggressive and metastatic type of malignant carcinoma that is associated with high mortality rates and is difficult to detect at early stages. Core 3 structure is a mucin-type O-glycans synthesized by β1,3-N-acetylglucosaminyltransferase 6 (core 3 synthase), which plays an important role in the digestive system, in particular gastrointestinal goblet cells. It has been reported that core 3 synthase-expressing cells show lower migratory and invasive rates, and lower metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…eCCAs are rare and show aggressive behaviors (2), and their clinicopathological characteristics vary depending on their anatomical location (7)(8)(9)(10). IES may be a hallmark of one type of extension in cancer biology, in which intraepithelial extension of cancer cells may be predominant over stromal invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…eCCAs are rare and show aggressive behaviors (2), and their clinicopathological characteristics vary depending on their anatomical location (7)(8)(9)(10). IES may be a hallmark of one type of extension in cancer biology, in which intraepithelial extension of cancer cells may be predominant over stromal invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the differences of clinicopathological characteristics of eCCAs dependent on anatomical location, eCCAs are currently categorized as perihilar and distal eCCAs to be evaluated in different tumor-node-metastasis (TNM) classifications (6). The accumulated findings suggest that the differences of eCCAs characteristics may be based on not only simply location differences but also biological properties of cancer cells raised in different anatomical locations (7)(8)(9)(10). Thus, further clinicopathological characterization and exploration of molecular alterations in eCCA are needed.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Radhakrishnan et al revealed that the expression of the core 3 structure of O-glycans affects the production and stability regulation of α1 and β2 integrin in pancreatic cancer, thus inhibiting metastasis [ 6 ]. Boottanun and colleagues reported that the low expression of B3GNT6 is associated with higher differentiation and better prognosis in patients with cholangiocarcinoma [ 7 ]. In prostate cancer, B3GNT6 inhibits tumor formation and metastasis through the downregulation of the α2-β1 integrin complex [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The core 3 structure is a kind of O-glycans which plays an important role in the differentiation of gastrointestinal goblet cells and the formation of mucosal barrier β Mucin type O-glycans synthesized by 1,3-N acetylglucosamine transferase 6 (core 3 synthase, β 3GnT6, C3GnT) ( 65 ). The core 3 structure is synthesized by β1,3-N-acetylglucosaminyltransferase 6 (B3GNT6 or core 3 synthetase), which adds GlcNAc with a β1,3-linkage to the Tn antigen (GalNAc alpha-serine/threonine), and since core 1 synthetase makes use of the same 3′-position of GalNAc found in the Tn antigen, the synthesis of core 3 may compete with core 1 synthesis ( 64 ).…”
Section: C1galt1 In Colorectal Cancermentioning
confidence: 99%
“…Normal colon mucosa predominantly express core 3 O-glycans ( 50 ). The absence of O-glycans compromises the colonic mucus barrier, leading to inflammation through the activation of caspase 1-dependent inflammasomes in colonic epithelial cells, a process mediated by the microbiota ( 65 ). Another research has shown a novel mechanism by which mucin-type core 3 O-glycan influences the epithelial-mesenchymal transition (EMT) and mesenchymal-epithelial transition (MET) plasticity of colorectal cancer (CRC) cells through a MUC1/p53/miR-200c-dependent signaling cascade ( 66 ).…”
Section: C1galt1 In Colorectal Cancermentioning
confidence: 99%